2021
DOI: 10.1177/15910199211024077
|View full text |Cite
|
Sign up to set email alerts
|

Twig-like middle cerebral artery: Embryological persistence or secondary consequences?

Abstract: We would like to comment on twig-like middle cerebral artery (MCA) in relation to the interesting article "Hemorrhagic events associated with unfused or twig-like configuration of the middle cerebral artery: A rare vascular anomaly with clinical relevance." by Dr. Viso et al. 1 in the April issue of our journal. In this article, the authors reported on twig-like MCAs identified in 9 patients (0.088%) and 62.5% of them were hemorrhagic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…The middle cerebral artery is formed by the fusion of reticulated vascular networks in utero [ 3 ]. It has been reported that this disease is caused by unknown factors hindering fusion in the M1 region and that a small network of vessels remains only in the horizontal region [ 3 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The middle cerebral artery is formed by the fusion of reticulated vascular networks in utero [ 3 ]. It has been reported that this disease is caused by unknown factors hindering fusion in the M1 region and that a small network of vessels remains only in the horizontal region [ 3 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Ap/twig-like MCA is based on angiographic imaging. Differentiation from moyamoya disease is particularly important for the diagnosis [ 3 , 6 , 8 ]. Unlike moyamoya disease, Ap/twig-like MCA is unilateral [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, common angiographical features of Ap/T-MCA are described as follows: 1) a steno-occlusive lesion can be seen on the unilateral MCA, 2) plexiform arterial network exists instead of the main MCA trunk, 3) perforators arise from the plexiform arterial network, and 4) cortical branches beyond the occluded MCA trunk have an anterograde flow with a normal configuration. [10][11][12] It is considered that MCA hypoplasia occurs because of the twig-like network remnants that exist at the time of MCA development. Reported characteristics of an Ap/T-MCA are stenosis or occlusive lesions confined to the unilateral M1.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to differentiate the two diseases; however, the following characteristics should be helpful: Ap/T-MCA is further characterized by normal vasculature beyond M2 and in other arteries, no collateral blood flow from the ECA, and no progression of the lesion. [10][11][12] Ap/T-MCA is a very rare condition, accounting for 0.11-1.17% of serial cerebral angiography cases, and is associated with bleeding events in more than half of these cases, with aneurysms often occurring in abnormal vessels. [6][7][8]13,14 The present case had the angiographical features of an Ap/T-MCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation